1994
DOI: 10.1002/ajh.2830470314
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow necrosis

Abstract: Bone marrow necrosis is most frequently diagnosed at postmortem examination. Antemortem diagnosis is still uncommon. In a recent review of world literature, we have found 133 cases of bone marrow necrosis diagnosed during life. It has been observed during the course of a wide variety of diseases, most commonly in association with acute and chronic leukemia, carcinoma, malignant lymphoma, infections, and sickle cell disease. We report two intravitally diagnosed cases of bone marrow necrosis occurring in two pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…5,7 It has been suggested that therapy for patients with BMN be aimed at promoting recovery of marrow stroma by the use of cytokines and chemotherapy not highly toxic to bone marrow stem cells and stroma. 2 In conclusion, our findings confirm that the conditions associated with BMN are varied and malignancy remains common. BMN may precede or obscure the diagnosis, and repeat biopsies are indicated to secure a diagnosis.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…5,7 It has been suggested that therapy for patients with BMN be aimed at promoting recovery of marrow stroma by the use of cytokines and chemotherapy not highly toxic to bone marrow stem cells and stroma. 2 In conclusion, our findings confirm that the conditions associated with BMN are varied and malignancy remains common. BMN may precede or obscure the diagnosis, and repeat biopsies are indicated to secure a diagnosis.…”
Section: Discussionsupporting
confidence: 78%
“…Likewise, laboratory findings seen in our patients and commonly associated with BMN include pancytopenia, microangiopathic features and a leukoerythroblastic blood picture. 2,3,7 Elevated serum lactate dehydrogenase and alkaline phosphatase levels are known associated laboratory features, 2,3,7 and were also seen in four of our patients ( Table 1). The prognosis of patients with BMN has been considered poor, 1,2 however, there have been reports of recovery in some cases with adequate supportive management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations